Learning Mathematics with the Geogebra Software Application - Sirait, Debora Exaudi; Silalahi, Mastiur Verawaty; Manik, Ria Retno; Situmorang, Masni Veronika; Siagian, Gunaria; Sirait, Erwin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mathematics is a subject whose field of study is abstract and requires the ability to think logically so that to convey it, a medium is needed so that students become more understanding of the material presented and stimulate students to improve their ability to think logically. One of the learning media that is in accordance with current developments is the use of software. Using the GeoGebra Software provides several advantages, including geometric drawings which are usually produced more quickly and accurately than using a pencil, ruler or compass. The existence of animation facilities and manipulation movements (dragging) in the GeoGebra Software can provide a clearer visual experience for students in understanding geometric concepts. Can be used as an evaluation to ensure that the painting that has been made is correct. Make it easier for teachers and students to investigate or show the properties that apply to a geogebraic object. The method used in this activity is an interactive lecture that is chosen to deliver software geoebra which is carried out in three stages, namely the field assessment stage, the implementation stage, and the evaluation stage. By using this GeoGebra software, it can increase the knowledge and understanding of teachers in learning mathematics and can produce teaching materials based on GeoGebra.